Experimental and Numerical Investigation of a Real Four-Story Building with an Open Ground Floor in a Seismic Region for Proper Strengthening - Iakov Iskhakov; Sharon Yehuda; Yuri Ribakov (Advances in Materials Science and Engineering, 2024)
Many existing buildings fail to meet the requirements of current earthquake resistance codes. Therefore, it is necessary to strengthen and/or upgrade such buildings. Strengthening and/or upgrading include adding new floors, parts, elements, etc. Modern codes usually do not reflect upgrading of existing buildings. These buildings may be damaged and require maintenance and repairs, which may change the original material and structural properties. Design of such buildings is based on dominant vibration periods obtained by empirical dependences according to the building codes or from dynamic numerical analysis using available software. In both cases, the results usually do not consider the present state of the structure, influence of nonstructural elements, and possible differences in material properties in various elements of the building due to construction problems, concrete creep, etc. Such evaluation can be done just based on dynamic analysis, experimental and numeric, whereas the first one is essential. Therefore, the present research is aimed at numerical and experimental investigation of an existing real multistory residential reinforced concrete building before its strengthening and/or upgrading according to the requirements of modern seismic codes. The present study is a first stage of the research. It is focused on obtaining the dynamic parameters of the building before its strengthening and upgrading. Experimental values of natural vibration periods and damping ratios are compared with those obtained numerically. Following these values, the design spectrum of the seismic code is updated and the building is designed using this updated spectrum. The findings of this study form a basis for the second research stage that will be aimed at monitoring and analyzing of this building at each stage of its strengthening and upgrading. This approach iaimed at improving the available techniques for strengthening and upgrading the building. It will also be the basis for further research in this direction.